Answer
3.) \( 4 \frac{3}{4} - 3 \frac{2}{3} = 1 \frac{1}{12} \)
4.) \( 5 \frac{3}{6} - \frac{2}{3} = 4 \frac{5}{6} \)
5.) \( 3 - 2 \frac{3}{5} = \frac{2}{5} \)
Solution
Sure, let's solve each of these subtraction problems involving mixed numbers step by step.
---
### **3.) \( 4 \frac{3}{4} - 3 \frac{2}{3} \)**
**Step 1: Convert Mixed Numbers to Improper Fractions**
- \( 4 \frac{3}{4} = \frac{4 \times 4 + 3}{4} = \frac{16 + 3}{4} = \frac{19}{4} \)
- \( 3 \frac{2}{3} = \frac{3 \times 3 + 2}{3} = \frac{9 + 2}{3} = \frac{11}{3} \)
**Step 2: Find a Common Denominator**
The least common denominator (LCD) for 4 and 3 is 12.
- \( \frac{19}{4} = \frac{19 \times 3}{4 \times 3} = \frac{57}{12} \)
- \( \frac{11}{3} = \frac{11 \times 4}{3 \times 4} = \frac{44}{12} \)
**Step 3: Subtract the Fractions**
- \( \frac{57}{12} - \frac{44}{12} = \frac{13}{12} \)
**Step 4: Convert Back to a Mixed Number**
- \( \frac{13}{12} = 1 \frac{1}{12} \)
**Final Answer:**
\( 4 \frac{3}{4} - 3 \frac{2}{3} = 1 \frac{1}{12} \)
---
### **4.) \( 5 \frac{3}{6} - \frac{2}{3} \)**
**Step 1: Simplify the Mixed Number**
- \( 5 \frac{3}{6} = 5 \frac{1}{2} \) (since \( \frac{3}{6} = \frac{1}{2} \))
**Step 2: Convert to Improper Fractions**
- \( 5 \frac{1}{2} = \frac{5 \times 2 + 1}{2} = \frac{10 + 1}{2} = \frac{11}{2} \)
- \( \frac{2}{3} \) remains the same.
**Step 3: Find a Common Denominator**
The LCD for 2 and 3 is 6.
- \( \frac{11}{2} = \frac{11 \times 3}{2 \times 3} = \frac{33}{6} \)
- \( \frac{2}{3} = \frac{2 \times 2}{3 \times 2} = \frac{4}{6} \)
**Step 4: Subtract the Fractions**
- \( \frac{33}{6} - \frac{4}{6} = \frac{29}{6} \)
**Step 5: Convert Back to a Mixed Number**
- \( \frac{29}{6} = 4 \frac{5}{6} \)
**Final Answer:**
\( 5 \frac{3}{6} - \frac{2}{3} = 4 \frac{5}{6} \)
---
### **5.) \( 3 - 2 \frac{3}{5} \)**
**Step 1: Convert to Improper Fractions**
- \( 2 \frac{3}{5} = \frac{2 \times 5 + 3}{5} = \frac{10 + 3}{5} = \frac{13}{5} \)
- \( 3 = \frac{15}{5} \) (to have the same denominator)
**Step 2: Subtract the Fractions**
- \( \frac{15}{5} - \frac{13}{5} = \frac{2}{5} \)
**Final Answer:**
\( 3 - 2 \frac{3}{5} = \frac{2}{5} \)
---
I hope this helps! Let me know if you have any other questions.
Reviewed and approved by the UpStudy tutoring team
Explain
Simplify this solution